IMPACT OF WORK ETHIC AND ORGANIZATIONAL COMMITMENT TO THE PERFORMANCE OF EMPLOYEES AT PT. POST INDONESIA (PERSERO) JEMBER BRANCH - Munir, Khoirul; Wijayantini, Bayu; Reskiputri, Tatit Diansari (Universitas Muhammadiyah Tangerang, 2024)
This research aims to examine the influence of work ethic variables (X1) and organizational commitment (X2) on employee performance (Y) at PT. Pos Indonesia (Persero) Jember Branch. PT. Pos Indonesia (Persero) Jember Branch operates in the field of delivery services, especially handling letters and packages for residents of Jember and its surroundings. Judging from its business activities, this company is included in the service-oriented business category. Using a quantitative research approach with descriptive methodology, this research focuses on a population of 59 PT employees.